Proposta de distribuição espacial de pontos de entrega voluntária para recebimento de resíduos de construção e demolição - Silva, Maria Aliny Souza (Universidade Federal Rural do Semi-Árido, 2020)
The improper disposal of construction and demolition waste results in negative impacts on the environment and, due to, on society. Therefore, the elaboration of public policies that will help waste management is extremely important. Within this context, through this research, the objective was to develop a proposal for the spatial distribution of voluntary delivery points for receiving construction and demolition waste in the municipality of Mossoró-RN. The methodology consisted of mapping the sites of inadequate disposal of construction and demolition waste in the urban area of the municipality through direct observation, comparing and applying methodologies to indicate the amount of voluntary delivery points needed, as well as indicating the appropriate areas for installing these equipment. Through the results obtained, it was conclude that spatial analysis is an important resource to locate suitable areas for the installation of urban equipment, facilitating the management waste, and that the implementation of voluntary delivery points is extremely necessary in view of the expressive number of areas inadequate disposal of construction and demolition waste identified in this research, totaling 897 points. At the end of this analysis, it was indicated the installation of 13 voluntary delivery points in the municipality of Mossoró.
Keywords: Obras; Resíduos; Sistema de informação geográfica; Construção civil; ENGENHARIAS::ENGENHARIA CIVIL